VD_FINDINFO Jug / 2017 / 370 vom 21. Juni 2017 - VD Tribunal cantonal (2017)
PRÉSOMPTION D'INNOCENCE, FIXATION DE LA PEINE, VOLDROIT PÉNAL, SURSIS À L'EXÉCUTION DE LA PEINE, REJET DE LA DEMANDE | 42 CP, 47 CP, 69 CP, 10 CPP (CH)